Edukasi Digital: Pentingnya meningkatkan kewaspadaan terhadap maraknya kejahatan siber di era digital - Nur, Adil Ferhan (Maliki Interdisciplinary Journal, 2026)
The rapid digital transformation has brought significant convenience across various sectors but also increased the risk of cybercrime threats. Data breaches, online fraud, and identity misuse indicate that public awareness of digital security remains low. This article aims to examine the importance of digital education in enhancing public vigilance against cybercrime in the digital era. This study applies a qualitative descriptive approach through literature analysis from four relevant academic journals and national regulations such as the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law). The findings reveal that structured digital education, cross-sector collaboration, and improved legal literacy form the foundation of cyber resilience within society. Therefore, strengthening community-based digital literacy programs is considered a strategic step in mitigating cybercrime risks in Indonesia.